Ten quick tips for creating an effective lesson. - Greg Wilson (PLoS Computational Biology, 2019)
We present 10 tips for building effective lessons that are grounded in empirical research on pedagogy and cognitive psychology and that we have found to be practically useful in both classroom and free-range settings.